Polymorphisms and haplotypes in the promoter of the TNF-α gene are associated with disease severity of severe fever with thrombocytopenia syndrome in Chinese Han population. - Bo Xing; Xiao-Kun Li; Shao-Fei Zhang; Qing-Bin Lu; Juan Du; Pan-He Zhang; Zhen-Dong Yang; Ning Cui; Chen-Tao Guo; Wu-Chun Cao; Xiao-Ai Zhang; Wei Liu (Public Library of Science (PLoS), 2018)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that is caused by a novel bunyavirus, SFTSV. We assessed whether the single nucleotide polymorphisms (SNPs) in the tumor necrosis factor-alpha (TNF-α) were associated with risk to severity of SFTS. Five TNF-α SNPs (SNP1: T-1031C; SNP2: C-863A; SNP3: C-857T; SNP4: G-308A; SNP5: G-238A) were genotyped in 987 hospitalized SFTS patients and 633 asymptomatic/mild SFTSV-infected subjects of Chinese Han origin. Multivariate logistic regression analysis was used to calculate adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs). The hospitalized SFTS patients had significantly lower frequency of G-238A A allele than those with mild/asymptomatic infection (P = 0.006). Furthermore, T-1031C C allele (P < 0.001) and G-238A A allele (P < 0.001) were significantly associated with decreased risk of death. Multiple haplotypes were significantly associated with decreased risk of SFTS hospital admission (SNP1-2, CC; SNP1-3, CCC; SNP1-4, CCCG; SNP1-5, CCCGA; SNP2-4, CCGA; SNP3-5, CGA; SNP4-5, GA) and death (SNP1-2, CA; SNP1-3, CAG; SNP1-4, CACG; SNP1-5, CACGG; SNP2-3, AC; SNP2-4, ACG; SNP2-5, ACGG) after correction for multiple comparisons. By using the ELISA assay, we observed that TNF-α concentration of hospitalized patients was significantly increased in acute phase than in convalescent phase (P < 0.001). Elevated TNF-α concentration was also revealed from fatal patients (P < 0.001). The -238A allele was associated with decreased serum TNF-α levels in SFTS patients in acute phase (P = 0.01). Our findings suggest that polymorphisms in TNF-α gene may play a role in mediating the risk to disease severity of SFTS in Chinese Han population.